Synthesis and Study Structural and Electrical Properties of Hg0.5Pb0.5-xSbxBa2Ca2Cu3O8+ Î´ Superconductors - Jasim, K. A.; Abdul-Nebi, M.; Ali, M. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Mercury-lead-antimony based superconductors with the formula Hg0.5 Pb0.5xSbxBa2Ca2Cu3O8+Î´ (x=0, 0.10 and 0.15) have been prepared by useing three step solid state reaction processes. Electrical resistivity, using four probe technique, is used to find the transition temperature Tc. It is found from that sample Hg0.5 Pb0.5Ba2Ca2Cu3O8.437 is semiconductor , sample Hg0.5 Pb0.4Sb0.1Ba2Ca2Cu3O8.353 is normal state with metallic behaviors, while sample Hg0.5 Pb0.35Sb0.15Ba2Ca2Cu3O8.233 is superconducting state with critical transition temperature (Tc) is 126K. X-ray diffraction (XRD) analysis showed a tetragonal structure with decrease in the c-axis lattice constant for the samples doped with Sb as compared with these which have no Sb content. It was found that the increase of  the Sb  concentrations of all our samples produce an increase of the volume fraction (Vphase) and decrease c/a and Mass density ÏM .